Harnessing PM2.5 Exposure Data to Predict Progression of Fibrotic Interstitial Lung Diseases Based on Telomere Length - Shull, Jessica Germaine; Planas-Cerezales, Lurdes; Lara Compte, Carla; Perona, Rosario; Molina-Molina, Maria (Frontiers in Medicine, 2022)
Cross-analysis of clinical and pollution factors could help calculate risk of fibrotic interstitial lung disease (ILD) development and progression. The intent is to build a body of knowledge around early detection and diagnosis of lung disease, harnessing new data sets generated for other purposes. We cross-referenced exposure levels to particulate matter 2.5 (PM2.5) with telomere length of a cohort of 280 patients with fibrotic ILD to weigh impact and associations. There was no linear correlation between PM2.5 and telomere length in our data sets as the value of the correlation coefficient is 0.08. This exploratory study offers additional insight into methodologies for investigating the development and prognosis of pulmonary fibrosis.